2021
DOI: 10.1038/s41598-021-84947-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Subfoveal Choroidal Thickness and Hypertensive Retinopathy

Abstract: The Beijing Eye Study 2011 is a population-based cross-sectional study in Northern China, which enrolled 3468 participants whose age were more than 50 years. A detailed ophthalmic examination was performed including spectral-domain optical coherence tomography with enhanced depth imaging for measurement of SFCT and fundus photography. Blood pressure, fundus photographs and choroidal OCT-images were available for 3237 (93.3%) subjects, with 1953 (56.3 ± 0.8%) of the study population fulfilled the diagnosis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“… 29 Furthermore, The Beijing Eye Study found that among patients with hypertension, those with hypertensive retinopathy, especially advanced stages, were associated with increased CT compared with hypertensive patients without ocular findings, which possibly implies the complex effects of different stages of hypertension on choroid. 30 On the contrary, Akay et al 31 have previously found that hypertensive patients with milder grades of hypertensive retinopathy (maximum grade 2) have thinner choroid that normotensive controls.…”
Section: Discussionmentioning
confidence: 96%
“… 29 Furthermore, The Beijing Eye Study found that among patients with hypertension, those with hypertensive retinopathy, especially advanced stages, were associated with increased CT compared with hypertensive patients without ocular findings, which possibly implies the complex effects of different stages of hypertension on choroid. 30 On the contrary, Akay et al 31 have previously found that hypertensive patients with milder grades of hypertensive retinopathy (maximum grade 2) have thinner choroid that normotensive controls.…”
Section: Discussionmentioning
confidence: 96%
“…However, subsequent studies have shown thinner choroidal ( 47 ) and retinal layers in hypertensive individuals ( 48 ). A more recent study concludes that increased subfoveal choroidal thickness was associated with hypertensive retinopathy but not the presence of systemic hypertension in the absence of ocular manifestations ( 49 ). Overall, the reported associations between OCT parameters and hypertension are conflicting, and interpreting the results together is hindered by varied cohort demographics, the use of different imaging devices, and inconsistently reported comorbidities and medication use.…”
Section: Discussionmentioning
confidence: 99%
“…The study group included 68 eyes of 34 adult individuals diagnosed with essential hypertension. Wei et al 20 showed that after correcting for age, sex, eye axis, lens thickness, anterior chamber depth, and other factors, subfoveal choroidal thickness (SFCT) was not significantly correlated with hypertension, but HR was correlated with choroidal thickness. However, SFCT only provides an estimate of the overall choroidal volume and does not reflect the choroidal vascular structure.…”
Section: Discussionmentioning
confidence: 99%